2022
DOI: 10.5194/egusphere-2022-1097
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of snow processes over the Western United States in E3SM land model

Abstract: Abstract. Seasonal snow has crucial impacts on climate, ecosystems and humans, but it is vulnerable to global warming. The land component (ELM) of the Energy Exascale Earth System Model (E3SM), mechanistically simulates snow processes from accumulation, canopy interception, compaction, snow aging to melt. Although high-quality field measurements, remote sensing snow products and data assimilation products with high spatio-temporal resolution are available, there has been no systematic evaluation of the snow pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Our previous study showed that ELM can well capture the snow distribution in the TP, compared to the MODIS remote sensing data, supporting the reliability of the results 28 . ELM simulations can reproduce the spatio-temporal pattern, interannual variability and elevation gradient for different snow properties over the WUS 58 . The simulations are in line with Snow Telemetry field measurements, MODIS remote sensing products, and data assimilation products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study showed that ELM can well capture the snow distribution in the TP, compared to the MODIS remote sensing data, supporting the reliability of the results 28 . ELM simulations can reproduce the spatio-temporal pattern, interannual variability and elevation gradient for different snow properties over the WUS 58 . The simulations are in line with Snow Telemetry field measurements, MODIS remote sensing products, and data assimilation products.…”
Section: Discussionmentioning
confidence: 99%
“…The model enhancements allow ELM to be used to investigate uncertainties related to model configurations on future snow projections. Our previous study showed that ELM can well capture the spatio-temporal distribution and interannual variability of snow properties and timing compared to field measurements, remote sensing observations, and data assimilated products 28,58 . These confirm the effectiveness of simulating snow processes in ELM.…”
Section: E3sm Land Modelmentioning
confidence: 99%